The 'Dinner Date' concept: Reconciliating the dating and hospitality industries - Hugues Séraphin; Omar Abou Hamdan (Journal of Tourism, Heritage & Services Marketing, 2023)
Purpose: This research note argues that investigating the intersections between hospitality and speed dating events can yield practical implications for both industries. Hospitality professionals can gain valuable insights into how to enhance customer experiences by understanding the unique needs and expectations of individuals participating in dating events. Conversely, dating event organizers can draw upon the principles of hospitality to create more engaging and enjoyable experiences for their attendees, ultimately contributing to the success and longevity of such events. Methods: Adopting the User-Centred Design (UCD), which is structured around seven distinct phases including understand, observe, engage, define, ideate, prototype and test, and implement. Results: This study suggests a blueprint for the new concept of speed dating event. It proposes a methodology to develop a research agenda to generate strategies for implementing the “dinner date” concept. Implications: Developing aligning goals between hospitality and dating industries creates a valuable experience for their target audience, where food is presented as a soft management tool facilitating this relationship.
Keywords: L83; G14; L80; 330; food and beverage; UCD framework; conviviality; customer experience